Informal-Formal Worker Wage Gap in Turkey: Evidence From A Semi-Parametric Approach - Yusuf Soner Baskaya; Timur Hulagu (European Regional Science Association (ERSA), 2011)
Using individual level data from Turkstat Household Labor Force Survey for 2005-2009 period and a variety of parametric and semi-parametric techniques, we test two hypothesis regarding formal and informal labor markets: whether there is a wage gap between formal and informal workers and whether this gap is sensitive to variations in unemployment rates across regions and over time, where the formality of employment is defined with respect to registry status of the individuals to compulsory Social Security System. In line with most studies, the formal workers earn more than informal workers, as suggested by standard wage regressions, conditional on workers' observed individual characteristics. On the other hand, considering the limitations of parametric methods and possibility of misleading results due to the different distributional characteristics of formal and informal workers, we alternatively implement propensity score matching. In contrast with the recent studies for other developing countries showing that the wage gap estimates with propensity score matching is insignificant, we do find large and sizable wage gaps between formal and informal workers in Turkey. While parametric methods give similar estimates for formal-informal wage gap within gender groups, the semi-parametric estimates suggest that the observed formal-informal wage gap is larger among females compared to males. Finally, we show that although the parametric methods, such as wage curve regressions, suggest that wages of informal workers decreases and wages of formal workers do not change with higher unemployment rates, the semi-parametric methods show that these gaps are insensitive to unemployment rate variations across regions or over time.
Keywords: C14; J30; J42; J60; O17; 330; Formal/Informal Employment; Wage Gap; Propensity Score Matching; Regional Labor Markets